2016
DOI: 10.1001/jamaoto.2016.1010
|View full text |Cite
|
Sign up to set email alerts
|

Upper Airway Computed Tomography Measures and Receipt of Tracheotomy in Infants With Robin Sequence

Abstract: Computed tomography measures quantifying tongue position and mandibular configuration can identify infants with Robin sequence, and importantly, differentiate those who have severe upper airway compromise requiring tracheotomy. Following validation, these measures can be used for objective upper airway assessment and for expediting clinical decision-making in these challenging cases for which no such tools currently exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…25 Lee et al demonstrated that infants with shorter tongue length as measured on computed tomography scan had a higher rate of tracheostomy. 26 In a prospective study of 8000 consecutive fetal ultrasounds, Bronshtein et al found 2 subjects with glossoptosis and confirmed this finding on postmortem examination. 12 These authors also identified glossoptosis on 4 ultrasound studies of fetuses suspected to have RS and corroborated these findings postnatally in all four.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…25 Lee et al demonstrated that infants with shorter tongue length as measured on computed tomography scan had a higher rate of tracheostomy. 26 In a prospective study of 8000 consecutive fetal ultrasounds, Bronshtein et al found 2 subjects with glossoptosis and confirmed this finding on postmortem examination. 12 These authors also identified glossoptosis on 4 ultrasound studies of fetuses suspected to have RS and corroborated these findings postnatally in all four.…”
Section: Discussionmentioning
confidence: 54%
“…Figueroa et al found differences in tongue shape on cephalometric radiographs of children under 2 years of age with RS compared with other groups . Lee et al demonstrated that infants with shorter tongue length as measured on computed tomography scan had a higher rate of tracheostomy . In a prospective study of 8000 consecutive fetal ultrasounds, Bronshtein et al found 2 subjects with glossoptosis and confirmed this finding on postmortem examination .…”
Section: Discussionmentioning
confidence: 93%
“…Also, the scout films from CT images can demonstrate the tongue base position. A sleep study is obtained, with the above caveats of a lack of normative data as well as the knowledge that any child with a cleft palate will have a higher likelihood of having an abnormal result 46,50…”
Section: Treatment – Surgical/invasive Management (Cleft/craniofacialmentioning
confidence: 99%
“…Computed tomography can be used to evaluate infant bony and soft tissue anatomy of the upper airway in 2 and 3 dimensions, which is not possible with cephalometrics [2729]. While CT scanning does require radiation exposure, maxillofacial CT is a routine preoperative examination for MDO [1618], so this evaluation method will not require additional exposure. Further, cone-beam delivery can markedly reduce total radiation dose, so there is no additional safety limitation for clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Cone-beam computed tomography (CBCT) allows for extensive anatomic characterization while avoiding excessive radiation exposure [14, 15]. At present, craniofacial CBCT is routinely used to determine the location of upper airway obstruction and depict the mandibular anatomy of infants with RS under consideration for surgical intervention [1619]. In this retrospective study, we identified quantitative parameters derived from CBCT images that differed between RS patients with normal or difficult intubation and tested their predictive efficacies by receiving operating characteristic (ROC) analyses.…”
Section: Introductionmentioning
confidence: 99%